Neurological features of newborns associated with late preterm and early term birth. - T. K. Mavropulo (Medičnì Perspektivi)
Infants delivered at 37 and 38 weeks’ gestation are at increased risk for morbidity as compared to infants delivered at 39-40 weeks. Our objectives were to study the frequency of transient neurologic dysfunction in the first months in newborns and infants, depending on the gestational age. We found a higher incidence of risk factors of pregnancy, more frequent need in oxytherapy after birth, and differences of hemo lyquordynamics at the age of 2-3 months.